If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1.5 + -0.5y) + 3y = 1 (1.5 * 2 + -0.5y * 2) + 3y = 1 (3 + -1y) + 3y = 1 Combine like terms: -1y + 3y = 2y 3 + 2y = 1 Solving 3 + 2y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 1 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 1 + -3 2y = 1 + -3 Combine like terms: 1 + -3 = -2 2y = -2 Divide each side by '2'. y = -1 Simplifying y = -1
| 8x+12y=120 | | 5(x+1)-7(9-x)=14 | | .8k+7=-0.7k+1 | | y^2+5=30 | | 0=-16t^2+32t+240 | | 8x^2+8x-60=0 | | -4a+8=4a | | 5x^2-14x-13=0 | | -6(5r+15)=600 | | 4x^2+4x-60=0 | | X^2-23x+22=0 | | S=.2(300-50) | | -21+5r=54 | | 2c(7c+5)=0 | | A^2-3ab-28b^2=0 | | -3a+9=3a | | 65=.2(w-40) | | (w+9)(w-15)=0 | | 13xy+18xy-20xy= | | 65=.2(w-10)4 | | 1+5y=8x-20 | | 4x+6x-17=2(2x+3x) | | -y+124=30 | | 9a+2=20 | | -t*42=3 | | 4a+12=4 | | -10m-8m=-24 | | 14/1+6/3 | | 1/2(6m-10)=3m-5 | | 27b+12b= | | 35=.2(255-10e) | | 3x+6=27+3 |